Ultra‐Sharp Circular Dichroism Induced by Twisted Layered C4 Oligomers. Issue 3 (29th January 2020) - Yang, Younghwan; Kim, Minkyung; Mun, Jungho; Rho, Junsuk
Abstract: Chiral metamaterials consisting of sub‐wavelength asymmetric unit cells exhibit different optical responses on circularly polarized states of incident light. Chiral metamaterials with strong chiroptical activities provide sensitive sensors, finer spectrometers, and high‐performance encryption techniques. With these advantages, many types of chiral metamaterials have been researched; twisted layered metamaterials and oligomers that consist of nanoparticles have been reported for engineered chiral properties. C4 chiral metamaterials minimize conversion of polarized states and oligomers support exotic resonant modes to enable chiral encoding. Twisted‐layered chiral metamaterials to connect optical properties between C4‐chirality and oligomers are described. These twisted‐layered chiral metamaterials have both properties of non‐conversion efficiencies from C4‐chirality and encodable circular dichroism spectra that are caused by relative positions of oligomers. They exhibit ultra‐sharp circular dichroism in the near‐infrared region. The sharp circular dichroism is induced by interactions among layers in the metamaterials. Characteristics of the interactions are analyzed by considering electric field distribution profiles. These chiroptical properties of the twisted layered chiral metamaterials may have wide applications, including spectroscopy, thermal detector, and biochemical distributors. Abstract : Well‐designed, twisted layered C4 oligomers have exotic optical activities. They exhibit non‐conversion efficiency and strong, ultra‐sharp circular dichroism in the near‐infrared region. Additionally, the oligomers have encodability with relative positions. This ultra‐sharp chiroptical activity can be used for spectroscopic applications. These properties are hard to obtain in pre‐researched metasurfaces due to the absorption of metal structures.